Coral reef sea cucumbers in Malaysia - Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah; Nordin, Noor Faizul Hadry; Hashim, Ridzwan; Usup, Gires (Marine Resources Division, 2010)
This study aims to document species presence and distribution of sea cucumbers (Echinodermata: Holothuroidea) in Malaysia. Several coral reef habitats in Peninsular Malaysia, West Malaysia and Sabah, East Malaysia were selected as study sites. In summary, the present data showed the-presence of 50 species of sea cucumbers from three orders and seven genera, with 34 species require further species identification. It was found that Order Aspidochirotida in general and genus Holothuria in particular were the major species classes. The most dominant species in Malaysia was Holothuria leucospilota. As many as 37 species were found in Sabah, 21 species were recorded in Peninsular Malaysia and 10 species were present in both regions. Of 15 Actinopyga species, 14 species recorded were from Sabah. These findings may be due to the extensive distribution of coral reefs and low level of marine pollution. However, the possibility of biogeography factors within and out of the Sunda Platform area cannot be ruled out. In contrast, low level of species diversity was observed in few study sites in Peninsular Malaysia especially in Langkawi Island possibly due to anthropogenic threats. Future studies including more study sites and molecular phylogeny are to be incorporated in order to obtain better view on the presence and distribution of sea cucumbers in Malaysia.